The Effect Of A Lemon And Honey Mask On Acne In Combined Injectable Contraceptive Users At The Rosida Family Planning Center Purwakarta In 2026 - Intan noor Khalifa; Yeni Tegar Setiawati; Evalina Fransisca Lusianawati (International Journal of Health and Pharmaceutical (IJHP), 2026)
Acne is a side effect that can be experienced by those taking combined contraceptive injections due to hormonal changes that increase sebum production on the facial skin. One alternative non-pharmacological treatment is a lemon and honey mask, which contains antibacterial, anti-inflammatory, and antioxidant properties.This study aimed to determine the effect of a lemon and honey mask on acne in those taking combined contraceptive injections at the Rosida Purwakarta TPMB in 2026. This study used a quasi-experimental method with a two-group pretest-posttest design. The study sample consisted of 64 respondents, consisting of an intervention group and a control group of 32 respondents each, using a purposive sampling technique. The intervention group was given a lemon and honey mask, while the control group received no special treatment. Data analysis used the Wilcoxon test.The results showed that before the intervention, most respondents experienced grade 2 acne. After administering the lemon and honey mask, the intervention group experienced a decrease in acne levels, with an increase in grade 1 acne of 22 respondents (68.8%). The statistical test results showed a p-value of 0.001 (p<0.05), indicating that the lemon and honey mask significantly reduced acne levels in those taking combination contraceptive injections.The lemon and honey mask is effective as a safe, easy, and economical non-pharmacological treatment alternative to help reduce acne in those taking combination contraceptive injections.